Summary of Best Evidence for Self-Management of Patients with Motor Dysfunction after Stroke - ZHENG Siting, HE Chunyu, ZHOU Jun, KONG Ye, YANG Xinyao, ZHOU Haiying, WEI Xiaofei (Zhongguo quanke yixue, 2023)
Background Self-management meets the long-term rehabilitation needs of stroke patients and their families. However, there is a lack of relevant evidence, and there is no scientific and standardized self-management program in clinical practice. Objective To evaluate and summarize the best evidence of self-management in patients with motor dysfunction after stroke. Methods PubMed, Cochrane Library, Web of Science, Embase, CINAHL, CNKI, Wanfang Data, VIP, Chinese Biomedical Literature Database (CBM), American Heart Association/American Stroke Association (AHA/ASA), World Stroke Organization (WSO), Chinese Stroke Association (CSA), Guidelines International Network (GIN), Scottish Intercollegiate Guidelines Network (SIGN), National Guideline Clearinghouse (NGC), and Yimaitong were searched for relevant research evidence on self-management of patients with motor dysfunction after stroke from inception to July 2022, including guidelines, expert consensuses, systematic reviews, quasi-experimental studies, and randomized controlled studies. Two researchers independently evaluated the quality of the retrieved literature by using the 2017 version of the Appraisal of Guidelines for Research and Evaluation (AGREE Ⅱ) and the 2016 version of the literature evaluation criteria developed by the Joanna Briggs Institute (JBI) Evidence-based Health Care Center, extracted evidence and graded the quality of the evidence to summarize the best evidence of self-management in patients with motor dysfunction after stroke. Results A total of 36 studies were involved, including 9 guidelines, 4 expert consensuses, 5 systematic reviews, 5 quasi-experimental studies, and 13 randomized controlled studies, which were summarized in 6 aspects of organization and management, assessment, exercise instruction, health education, psychological support, monitoring and follow-up, and 34 pieces of best evidence. Conclusion The evidence of self-management in patients with motor dysfunction after stroke summarized in this study contains 6 aspects: organization and management, assessment, exercise instruction, health education, psychological support, monitoring and follow-up. Healthcare workers should select the best evidence based on the individual situation and needs of patients in the context of clinical practice, and provide personalized self-management interventions for patients, so as to improve their motor function and self-management ability, promoting the recovery of disease.